Alteraciones electroquímicas en suelos cultivados con arroz bajo condiciones de riego - Sánchez Morán, Alexander Joel (2021)
Rice is one of the most cultivated and consumed cereals in the world and plays a strategic role in the agri-food chain. Rice is the main source of carbohydrates for more than half of the world's population and is consumed by people with high and low purchasing power. Understanding the influence of floods on the electrochemical and chemical properties of soils provides necessary information in their management for rice production. With this objective, a review was carried out to understand the electrochemical alterations in soils cultivated with rice under irrigated conditions. Irrigated soils differ widely in their abilities to release ammonium, P, K, Ca, Mg, Fe, Mn, and Zn and therefore an analysis can provide useful information on potential plant nutrient deficiencies as well as on the appearance of Fe toxicity in soils with irrigated rice. Dissolved inorganic nitrogen (DIN) adsorbed on soil colloids plays an important role in the leaching of N from the soil. In general, the review shows that flooded soils affect electrochemical and chemical processes which, in turn, dynamically affect soil fertility. The widespread adoption of the use of low-loss N sources could become a key solution for the future reduction of environmental pollution by N and agricultural N inputs.